Pengaruh E-money dan Gaya Hidup terhadap Perilaku Konsumtif Mahasiswa - Susy Magfirah Urbubiyah; Annisa Warastri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the influence of e-money and lifestyle on the consumptive behavior of students in Yogyakarta. The method used is quantitative correlational with a sample of 266 active students. Data were collected using scales for e-money, lifestyle, and consumptive behavior, and analyzed through regression analysis. The results show that lifestyle significantly influences students' consumptive behavior, while e-money does not have a significant effect. These findings indicate that although the use of e-money provides convenience, students' lifestyle plays a more dominant role in shaping their consumptive behavior. Other factors not covered in this study may also influence consumptive behavior.